The Impact Of Psychological Relationships Between Teachers And Students On Educational Effectiveness (Eurasian Journal of Learning and Academic Teaching, 2026)
In this article, the importance of psychological relationships between teachers and students in the educational process is analyzed. The role of a positive psychological environment, pedagogical communication, emotional support, and mutual trust in improving educational effectiveness is examined from a scientific perspective. In addition, the impact of negative relationships on students’ motivation, activity, and psychological state is also considered.